Suitability of Self‐Reducing and Slag‐Forming Briquettes for Electric Arc Furnace Use Based on Laboratory Tests. Issue 2 (1st February 2022) - Abdelrahim, Ahmed; Aula, Matti; Iljana, Mikko; Willms, Thomas; Echterhof, Thomas; Steinlechner, Stefan; Mombelli, Davide; Mapelli, Carlo; Omran, Mamdouh; Preiss, Stefan; Fabritius, Timo
Abstract : The in‐plant recycling routes of several side streams produced in Electric Arc Furnace (EAF) steelmaking remain under‐explored. In article 2100472, Abdelrahim and co‐workers characterize eight side streams and use them to produce seven different briquettes. Briquettes are assessed for their suitability to be used in EAF through a series of mechanical and high‐temperature tests, reflecting their intended use.